2020
DOI: 10.1055/a-1147-9124
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effects of Kinesio Taping on pain in Athletes with Patellofemoral Pain Syndrome

Abstract: Background Ligaments injury and anterior knee pain is the most common problem in the knee joint. In practice, there are various interventions for the treatment of patellofemoral pain syndrome (PFPS). Kinesio taping is one of them, but little literature is available on the immediate effects of treating this problem. Methodology From June to September 2017, a randomized control study was conducted at the Army Sports Complex GHQ Rawalpindi to determine the effectiveness of Kinesio Taping (KT) in patellofemoral pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In this study, there was a significant difference in the change of the pressure pain thresholds in both groups, and the KTLT group showed significant improvement from 64.33 ± 16.79 lb to 72.31 ± 15.38 lb compared to the CON group.This was consistent with the results of Donec et al [14] who applied to Kinesio taping to patients with knee osteorthritis and compared that with sham Kinesio taping treatment and reported a significant decrease in knee pain, and Rahlf et al [31] reported that there was a significant difference in WOMAC pain score when Kinesio taping was applied to osteorthritis patients and compared with sham treatment. And in a study by Rehman et al [32] immediate knee taping had a positive effect on knee pain reduction in athletes. Also, Paolillo et al [24] noted that there was a significant improvement of pressure pain threshold by conducting ultrasound and LLLT, which supported the results of this study.…”
Section: Discussionmentioning
confidence: 92%
“…In this study, there was a significant difference in the change of the pressure pain thresholds in both groups, and the KTLT group showed significant improvement from 64.33 ± 16.79 lb to 72.31 ± 15.38 lb compared to the CON group.This was consistent with the results of Donec et al [14] who applied to Kinesio taping to patients with knee osteorthritis and compared that with sham Kinesio taping treatment and reported a significant decrease in knee pain, and Rahlf et al [31] reported that there was a significant difference in WOMAC pain score when Kinesio taping was applied to osteorthritis patients and compared with sham treatment. And in a study by Rehman et al [32] immediate knee taping had a positive effect on knee pain reduction in athletes. Also, Paolillo et al [24] noted that there was a significant improvement of pressure pain threshold by conducting ultrasound and LLLT, which supported the results of this study.…”
Section: Discussionmentioning
confidence: 92%